Light Microscopic Studies on the Alcoholic Rat Testes - Cengiz, Nureddin; Otlu, Ali (Fırat University, 2002)
Aim: To evaluate the testicular changes in rats in chronic alcohol intake with liquid diet. Material and Methods: In this study adult male Wistar rats were used. They were fed by a modified liquid diet containing 7.2 % of ethanol for 60, 120 and 180 days. The rats in the control groups were also fed by the same liquid diet without alcohol. At the end of the experiment the rats were sacrificed by cervical dislocation. Testes was dissected and fixed in Bouin's solution and the sections were stained with hematoxylin-Eosin staining technique for histological evaluations. Results: Histochemical staining demonstrated, decreased body weight gain, gonadal atrophy, desquamated spermatocytes in the lumen of seminiferous tubules, in the cytoplasm of the Leydig cells deposits of fat droplets and tubular degenerations when compared with control in the alcoholic groups. Conclusion: The intensification of the above described changes were observed to bedependent on the duration period of alcohol intoxication. These testicular changes might be due to malabsorbtions, lipid peroksidations and endocrine imbalance.

Amaç: Deneysel bir model üzerinden ratlarda kronik alkolizm oluşturularak testis dokusunda alkole bağlı olarak gelişen değişiklikler araştırıldı. Gereç ve Yöntem: İki, dört ve altı ay süre ile % 7.2 alkol içeren modifiye bir sıvı diyetle beslenmeye tabi tutulan ergin Wistar albino erkek ratların kontrol gruplarına alkolsüz izoenerjik sıvı diyet uygulandı. Sakrifiye edilen deneklerin testis dokuları Bouin's solusyonunda tesbit edildi. Doku takip işlemlerinden sonra parafine gömülen örneklerden 5-7 mm kalınlığında alınan kesitlere histolojik değerlendirmeler yapmak amacıyla hematoxylin-eosin boyama metodu uygulandı. Bulgular: Kontrol grubuyla karşılaştırıldığında alkol grubu deneklerde; daha az ağırlık kazanımı, testiküler atrofi, spermatojenik hücre dökülmesi, sertoli hücre sıklığı, yağlanma ve tubuler dejenerasyonlara varan değişiklikler izlendi. Sonuç: Zamanla artan bu değişikliklerin malabsorbsiyon-lardan, besinlerin biyolojik yararlanımındaki azalmadan, lipit peroksidasyonu ve endokrin imbalanstan kaynaklanabileceği sonucuna varıldı.
ALKOLİK RAT TESTİSLERİ ÜZERİNDE IŞIK MİKROSKOPİK ARAŞTIRMALAR